Unveiling DNA methylation: early diagnosis, risk assessment, and therapy for endometrial cancer - Li, Minzhen; Xia, Zhili; Wang, Ruiyu; Xi, Mingrong; Hou, Minmin (Frontiers in Oncology, 2025)
Endometrial cancer (EC), one of the most common gynecologic malignancies worldwide, poses a significant burden particularly among young women, with poor treatment outcomes and prognosis for advanced and recurrent patients. Epigenetic changes, encompassing DNA methylation, are involved in the occurrence and progression of tumors and hold promise as effective tools for screening, early diagnosis, treatment strategy, efficacy evaluation, and prognosis analysis. This review provides a comprehensive summary of DNA methylation-based early diagnostic biomarkers in EC, with a focus on recent valuable research findings published in the past two years. The discussion is organized according to sample sources, including cervical scraping, vaginal fluid, urine, blood, and tissue. Additionally, we outline the role of DNA methylation in EC risk assessment, such as carcinogenesis risk, feasibility of fertility preservation approaches, and overall prognosis, aiming to provide personalized treatment decisions for patients. Finally, we review researches on DNA methylation in resistance to first-line treatment of EC and the development of new drugs, and envision the future applications of DNA methylation in EC.